The discovery of novel proteins regulating melanosome biogenesis and function - Detry, Anna, author; Di Pietro, Santiago, advisor; Hansen, Jeffrey, committee member; Hoerndli, Frederic, committee member (Colorado State University. Libraries, 2022)
Melanosomes are lysosomal related organelles found in cells which are responsible for making pigment such as skin melanocytes. They are membrane bound organelles that form from the endosomal pathway and have specific proteins and enzymes which allow them to perform the function of melanin production. The process of melanosome biogenesis involves the melanosomes developing through four stages that are classified by electron microscopy appearance. The different melanosome stages have amyloid fibrils formed by proteolytically processed PMEL protein, different amounts of melanin, and different melanosomal proteins. In addition to melanosome biogenesis, another key factor in proper melanin formation and pigmentation is the melanosome luminal pH. The melanin producing enzyme tyrosinase is a pH dependent enzyme. When melanosomes are more acidic, tyrosinase is less functional, leading to less melanin production and a hypopigmentation phenotype. The Di Pietro lab and others have shown that the Two Pore Channel Two (TPC2) is a key regulator of melanosome pH, as well as a regulator of melanosome size and localizes to melanosome membranes. A proximity-dependent biotin identification experiment was preformed using TPC2 and eight potential melanosome proteins were identified. Each of these candidate proteins were knocked down in a human melanoma cell line using small interfering RNA and studied for a potential pigmentation phenotype. Tetraspanin10, phospholipase D1, myosin heavy chain 9, and myosin heavy chain 10 all showed a hypopigmentation phenotype. Two independent tetraspanin 10 knockout cell lines were generated using CRISPR-Cas9 which reproduced the hypopigmentation phenotype. In addition, the phenotype was rescued by re-expressing tetraspanin 10 in the knockout cells and overexpressing tetraspanin 10 in wild type cells showed a hyperpigmentation phenotype. This shows that tetraspanin 10 is involved in the pigmentation process. CD63 is another tetraspanin known to play vital roles in melanosome biogenesis and based on the minimal information aviable on tetraspanin 10, it can be hypothesized as being involved in PMEL processing. The discovery that tetraspanin 10 is involved in skin pigmentation will lead to better understanding of the pigmentation process and pigmentation related diseases.
Keywords: melanosomes; PLD1; melanocyte; TSPAN10; pigment